Analysis of Financial Performance Comparison Using the Economic Value Added (EVA) and Financial Value Added (FVA) Methods - Sabila, Suci; Widuhung, Sisca Debyola (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to determine and analyze the financial performance of Sharia Commercial Banks (BUS) listed on the Indonesia Stock Exchange (BEI) using the Economic Value Added (EVA) and Financial Value Added (FVA) methods for the period 2018 – 2022. This type of research is quantitative descriptive research, and the population in this study consists of all BUS listed on the BEI. The data used in this study are secondary data derived from the annual reports of each audited bank. The hypothesis test used is non-parametric analysis, namely the Mann-Whitney U test. This study concludes that EVA and FVA in BUS listed on the BEI during the period 2018 – 2022 overall show positive figures and can be considered to have good financial performance.